Product design of can opener by using effort flow analysis approach - Teoh, Jin Shen (2007)
In this project, Effort Flow Analysis has been carried out on can opener. The can opener available in market are usually manufactured in many parts that is including manufacturing cost and assembly time have been wasted, this factor create opportunity the product evolution of can opener for engineer to invent simple can opener with minimized parts. The evolution of can opener in a new proposed design creates an opportunity to manufacturing of can opener with low assembly cost and labor time saving which is very important to industry nowadays. The new proposed design is functional and very user friendly for customer. Before the Effort Flow Analysis has been done, preliminary finding of can opener parts must be implemented to determine the goal of product evolution. After the Effort Flow Analysis has been done, brainstorming on modeling is carried out, using the result of analysis as guidance. The proposed design will be compare with original design by using Design for Assembly tool, Boothroyd and Dewhurst method, to determine the assembly cost and labor time. The proposed design will refine into fabrication prototype to compromise with the manufacturing process. The prototype will be fabricated with Rapid Prototyping machine which is very suitable for prototyping products. From the analysis and design, the results of this project will be reported.